2014
DOI: 10.1007/s10461-014-0965-y
|View full text |Cite
|
Sign up to set email alerts
|

Communication About Microbicide Use Between Couples in KwaZulu-Natal, South Africa

Abstract: The ways in which couples communicate about microbicides is likely to influence microbicide uptake and usage. We collected quantitative data about whether women in a microbicide trial discussed microbicides with their partners and explored communication about microbicides during 79 in-depth-interviews with women enrolled in the trial and 17 focus-group discussions with community members. After 4 weeks in the trial, 60 % of 1092 women had discussed microbicides with their partners; in multivariate analysis, thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 54 publications
1
13
0
Order By: Relevance
“…M. Montgomery et al, 2010), some men increasingly regulated their partners' sexual lives and the use of the gel because of their fear that their partners may use it with other men for sexual pleasure. The findings are consistent to some extent with Gafos et al (2015)'s study in South Africa in as far as women in long term relationships are concerned. However, Gafos et al (2015)'s study suggests that young couples reported more autonomous use of gel because they were more likely to be in less established relationships where issues of trust and informing the male partners were less important.…”
Section: Discussionsupporting
confidence: 89%
“…M. Montgomery et al, 2010), some men increasingly regulated their partners' sexual lives and the use of the gel because of their fear that their partners may use it with other men for sexual pleasure. The findings are consistent to some extent with Gafos et al (2015)'s study in South Africa in as far as women in long term relationships are concerned. However, Gafos et al (2015)'s study suggests that young couples reported more autonomous use of gel because they were more likely to be in less established relationships where issues of trust and informing the male partners were less important.…”
Section: Discussionsupporting
confidence: 89%
“…However, study findings also suggest that many women will likely talk with their partners about using microbicides. In all clinical trials and surrogate studies that asked about partner communication, participants typically talked with steady partners about their microbicide use at some point during study participation [ 12 , 14 , 30 , 32 , 37 , 42 , 61 , 66 , 69 ].…”
Section: Resultsmentioning
confidence: 99%
“…Deciding whether to talk to a partner about microbicide use may be more complicated for women in violent or abusive relationships. If a woman tries to use a gel product without her partner's knowledge and her partner finds out, he may react violently [ 13 , 30 , 61 , 69 , 71 ]. Some women may decide to communicate with their partner about microbicide use because they fear a negative or violent reaction if their partner discovers they have been using a product without discussing it first [ 20 , 69 ].…”
Section: Resultsmentioning
confidence: 99%
“…Gender dynamics and expectations for sexual relationships and experiences are vital aspects of the context within which sex occurs [7, 13, 14] and, as such, for understanding women’s experience of the ring. In sub-Saharan Africa, where young women are at especially high risk for contracting HIV [15], there is increasing exposure to and emphasis on “modern,” powerful and independent women, especially in urban centers.…”
Section: Introductionmentioning
confidence: 99%
“…In sub-Saharan Africa, where young women are at especially high risk for contracting HIV [15], there is increasing exposure to and emphasis on “modern,” powerful and independent women, especially in urban centers. Nonetheless, predominant feminine identities are associated with “traditional” female roles that accept male authority and comply with requests and desires of male partners [13, 14, 1618], which extends to male decision making in regard to sexual activity and methods to prevent HIV transmission [14, 19]. …”
Section: Introductionmentioning
confidence: 99%